THE COMPETITIVE SOCIAL ADVANTAGES OF A COUNTRY AND ITS COMPETITIVE POSITION: A COMPARATIVE ANALYSIS - Chornodid, Ihor S. (Ekonomika, 2014)
Abstract. In the article, the concept of competitive social advantages is considered. Social competitiveness, the potential of social competitiveness, and the social competitive status are characterized. Competitive advantages are shown to have various forms of expression due to certain determinants. A classification of competitive advantages is carried out. The framework of competitive advantages is described. The determinants of competitive social advantages of a country, among which the components of the level and quality of life, the maturity of the human, intellectual and social capital, the quality of public institutions, conditions of business development and innovations are suggested. The trends and means of achieving social competitive advantages are considered. The assessment of Ukraine’s position according to freedom indicators, the indicator of network readiness, Ukraine’s competitiveness index and index of travel and the tourism competitiveness is conducted.Key words: social competitiveness, social advantages, competitive social advantages, social potential, social capital